Roscovitine blocks collecting duct cyst growth in Cep164-deficient kidneys - Airik, Rannar; Airik, Merlin; Schüler, Markus; Bates, Carlton M.; Hildebrandt, Friedhelm (Kidney International, 2019)
Nephronophthisis is an autosomal recessive kidney disease with high genetic heterogeneity. Understanding the functions of the individual genes contributing to this disease is critical for delineating the pathomechanisms of this disorder. Here, we investigated kidney function of a novel gene associated with nephronophthisis, CEP164, coding a centriolar distal appendage protein, using a Cep164 knockout mouse model. Collecting duct-specific deletion of Cep164 abolished primary cilia from the collecting duct epithelium and led to rapid postnatal cyst growth in the kidneys. Cell cycle and biochemical studies revealed that tubular hyperproliferation is the primary mechanism that drives cystogenesis in the kidneys of these mice. Administration of roscovitine, a cell cycle inhibitor, blocked cyst growth in the cortical collecting ducts and preserved kidney parenchyma in Cep164 knockout mice. Thus, our findings provide evidence that therapeutic modulation of cell cycle activity can be an effective approach to prevent cyst progression in the kidney.
CRIS-Team Scopus Importer:2019-07-02
Keywords: centrosome; CEP164; cilia; nephronophthisis; polycystic kidney disease